REPORT MANAGEMENT SYSTEM OF EARLY WARNING ALERT AND RESPONSE SYSTEM PROGRAM EVALUATION, TANAH BUMBU DISTRICT - Dicky Andiarsa; Deni Fakhrizal; Syarif Hidayat; Gusti Meliyanie; Harninda Kusumaningtyas; Yuniarti Suryatinah (Universitas Airlangga, 2022)
Background: The threat of outbreaks of infectious diseases is getting significant attention worldwide, and WHO requires all countries to increase early awareness and respond quickly. Indonesia has built a system called the Early Warning Alert and Response System (EWARS) which may detect any threat of an indication of an infectious disease outbreak computerized reported weekly. Purpose: This study aims to evaluate to systematically assess the data management and reporting system for implementing the EWARS. Methods: The evaluation research conducted interviews with EWARS officers at all levels of the Health Office in Tanah Bumbu District in September-November 2020. This study evaluated the implementation of EWARS, which was variable was a verification of reporting data and a management system with descriptive analysis using a spreadsheet instrument. Results: The instrument results showed that the strengths and weaknesses of SKDR implementation data management lie in the low ability of managers to translate instructions, less active monitoring from the supervisor, and the officers have not been trained. The verification in the total cases reported were gaps in the data from the aggregate district health office, Puskesmas, to Service Delivery Points due to unverified. Reporting performance during the assessment period of the Tanah Bumbu District Health Office was abysmal due to unscheduled and incomplete. The reporting and feedback performance cannot give a clear appeal, instruction and/or warning to a more deficient unit. Conclusion: The reporting performance of EWARS officers and EWARS management was poor and improvement needed.